Statistical exploration of factors associated with birth of children having sickle cell traits among reproductive-age women in Nigeria - Gabriel Ogunde; Ayodele Shabi; Joshua O. Akinyemi (BMC Public Health)
Abstract Background Despite the relatively high prevalence of Sickle cell trait (SCT) in Nigeria, there has been little research into the correlates of having children with SCT among Nigerian mothers, particularly in terms of socio-demographic differentials. This study aims to investigate the maternal socio-demographic correlates of having under-five children with SCT in Nigeria. Method Data from the 2018 Nigeria Demographic and Health Survey (Household Person Recode and Children Recode) were merged. Mothers with at least one under-five child whose genotype was known (n = 7,493) served as the unit of analysis. Three forms of outcome variable were explored. First was the number of children with SCT by each mother. Second, the number of children with SCT was categorized as zero, one, two or more. Lastly, each mother was categorized as either having no child(ren) with SCT or having at least one child with SCT. Subsequently, we assessed multilevel Poisson, ordinal and binary logit models to identify the best fitting model using Akaike and Bayesian Information Criterion. Multilevel binary logistic regression model was identified as best fit used to identify factors associated with having children with SCT. Adjusted Odds Ratio with 95% Confidence Interval (CI) were reported as measures of association. Result Nearly 62% of the mothers lived in rural areas, 38.2% had no formal education and 37.4% had ever given birth to at least five children. About 26.1% (95% CI = 25.2–26.9) of the mothers had children with SCT. By geographical variation, the Northwest region had the highest proportion of mothers of under-five children with SCT. Results from the multilevel binary logistic regression revealed that women who were traditionalists (AOR = 1.77; 95% CI = 1.04–3.02) were more likely of having children with SCT. Conclusion Though SCT is a genetic outcome, findings from this study suggest that important socio-demographic factors such as religion, and region of residence are significantly associated with having children with SCT in Nigeria. Sustained efforts on awareness campaigns on SCT are recommended.